2020
DOI: 10.9734/ejnfs/2020/v12i1030303
|View full text |Cite
|
Sign up to set email alerts
|

Potentiality of Fractionated Extracts from Hemizygia welwitschii Rolfe-Ashby (Lamiaceae) Leaf to Protect Maize against Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) in Storage

Abstract: Laboratory tests were conducted in order to assess the potential insecticidal effect of hexane, acetone and methanol fractionated extracts from Hemizygia welwitschii leaves against Sitophilus zeamais Motschulsky, important stored maize pest. The three extracts used individually were applied at four different concentrations (2, 4, 6 and 10 g/kg of maize) against the weevil. The efficacy of the treatment was evaluated by recording adult mortality after 1, 3, 7 and 14 days of infestation, and the F1 progeny emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Ignacimuthu et al, (2000) and Mainali et al, (2015) demonstrated that C. chinensis females employ chemical information during both host-seeking and acceptance. Also, results in the present study coupled with those by (Babu et al, 2003Beck et al, 2012Li et al, 2012) (Fotso et al 2018) or volatile oils (Fotso et al (2019) of Hemizygia welwitschia also significantly reduced the production and inhibited F1 progeny emergence of C. maculatus. Also, volatile oils of the Lamiaceae, Ocimum canum (Kosini et al, 2015) and Plectranthus glandulosus (Danga et.al., 2015) offer a significant reduction in seed damage activity compared with the untreated seeds.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Ignacimuthu et al, (2000) and Mainali et al, (2015) demonstrated that C. chinensis females employ chemical information during both host-seeking and acceptance. Also, results in the present study coupled with those by (Babu et al, 2003Beck et al, 2012Li et al, 2012) (Fotso et al 2018) or volatile oils (Fotso et al (2019) of Hemizygia welwitschia also significantly reduced the production and inhibited F1 progeny emergence of C. maculatus. Also, volatile oils of the Lamiaceae, Ocimum canum (Kosini et al, 2015) and Plectranthus glandulosus (Danga et.al., 2015) offer a significant reduction in seed damage activity compared with the untreated seeds.…”
Section: Discussionsupporting
confidence: 67%
“…Also, results in the present study coupled with those by Chudasama et al (2015), Kosini and Nukenine (2017) and Mahama et al (2018) suggest that leaf powder extracts are highly effective in controlling bruchids infestations. Hertlein et al (2011) and Fotso et al (2018) demonstrated that, effective control of protectants is attributed to the mortality of adult and/or immature stages, confirmed by lack of progeny generation. According to Fotso et al (2019) the efficacy of these botanical methods could be attributed to the presence of some bioactive compounds, including phenolic compounds, alkaloids, saponins, tannins, flavonoids, triterpenoids, and sterols.…”
Section: Discussionmentioning
confidence: 98%
“…It was reported that P. guineense had the highest larvicidal effect and lower productivity. Also, a study by Fotso et al (2018) investigated the efficacy of Hemizygia welwitschii leaf powders against C. maculatus and Sitophilus zeamais in stored cowpea and maize. The use of plant materials for grain preservation, particularly against cowpea beetle C. maculates is considered to be a promising alternative to synthetic insecticides (Boeke et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The hexane extract from goat weed ( Ageratum conyzoides ) showed insecticide activity against coleoptera pests of stored products with LD 50 of 2.72–39.71 mg⋅g −1 , but ethanol extract ( Moreira et al., 2007 ). Fotso et al. (2020) revealed that all the tested Hemizygia welwitschii leaf extracts exhibited insecticidal action against maize weevil, which was more susceptible to the hexane extract than acetone extract.…”
Section: Discussionmentioning
confidence: 99%